Analysis of the Development of an Investment Risk Assessment Model at Bank Syariah Indonesia, Tamalanrea Branch, Makassar City - Syarifuddin, Syarifuddin (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2025)
Sharia financial institutions play an important role in identifying, measuring, and managing risks related to operations and financial products to ensure compliance with sharia principles. This study aims to determine how customer investment risk is developed at Bank Syariah Indonesia (BSI) and what is the appropriate evaluation model to address the risks that occur when investing in Bank Syariah Indonesia (BSI) Tamalanrea Branch, Makassar City. This study uses qualitative research with a descriptive approach and data collection methods through observation and interviews, as well as analysis tools that utilise data reduction. The results of the study show that, first, the development of investment risk in Islamic banks includes financing, market, and reputation risks, which must be managed effectively through comprehensive risk management. Second, the appropriate evaluation models to address the risks that occur when investing in the Indonesian Islamic Bank (BSI) Tamalanrea Branch in Makassar are Risk-Adjusted Return on Capital (RAROC) and Value at Risk (VaR), which are proposed to improve the bank's performance and transparency. This study provides insight into the importance of risk management techniques in supporting the growth and sustainability of Islamic banking in Indonesia.